The Objectification of the Covered: Understanding Muslim Female Students’ Passivity in Physical Activities - Zahara, Difa Mahya (Muslim Education Review, 2023)
Patriarchal culture in Indonesia affects vast aspects of social life, including in schools where students acquire an understanding of gender. One of the prominent gender issues in social encounters within a patriarchal culture is the uniquely female experiences of objectification at school. This article draws on data from a qualitative study on Muslim female students in an Indonesian Islamic Middle School to understand female students’ experience of objectification by applying a psychosocial feminist objectification theory (Fredrickson and Robert, 1997). The study finds that non-sexual objectifying treatment from male peers is manifested in male gazes and comments on women’s general physical appearance, and specifically on Islamic apparel—the veil and modest Muslim style clothing. More direct sexual objectification occurs in the form of male gazes and sexual comments on certain body parts, such as the chest and hips. These experiences are understood by female students’ male-centered understanding of the Islamic feminine ideal which contributes to their withdrawal from physical activities at school as in Physical Education and art performance courses. This research argues for separate PE classes as a temporary alternative for the sake of female students’ participation.